Development of Entrustable Professional Activities for Advanced Inflammatory Bowel Disease Fellowship Training in the United States. Issue 9 (20th August 2020) - Cohen, Benjamin L; Gallinger, Zane R; Ha, Christina; Holubar, Stefan D; Hou, Jason K; Kinnucan, Jami; Mahadevan, Uma; Moss, Alan C; Raffals, Laura E; Regueiro, Miguel; Szigethy, Eva; Wolf, Douglas; et al.
Abstract : Ten entrustable professional activities for advanced IBD fellowship were developed by a multisociety task force through a multistep approach defining the essential tasks of an IBD-focused gastroenterologist to be mastered during advanced training. Abstract: Background: The level of inflammatory bowel disease (IBD) training in general gastroenterology fellowship is often insufficient to prepare trainees to deliver advanced IBD care in practice. Advanced IBD fellowships have been developed to fill this training gap, but there is no established curriculum, and significant variability exists across programs. Entrustable professional activities (EPAs) are practical and realistic objectives that define essential tasks of a specialty that physicians should master to be competent during independent practice. The American College of Gastroenterology (ACG) and Crohn's & Colitis Foundation (Foundation) established a task force to develop and appraise EPAs for advanced IBD fellowship. Methods: Entrustable professional activities were developed using a multistep approach in a similar manner to other specialties. Initial EPAs identified via focus groups were evaluated, critiqued, and changed using an iterative model of feedback. The final EPAs were selected after the task force conducted a 3-phase modified Delphi method consisting of 2 sequential rounds of web-based voting and an in-person consensus meeting. Results: Ten EPAs for advanced IBD fellowship were established including detailed descriptions with the associated knowledge, skills, and attitudes for each that can serve as curricular milestones. Conclusion: Ten EPAs describing the core work of an advanced IBD fellowship–trained physician have been established by a multisociety task force. Creating EPAs for an advanced curriculum comes with unique challenges, particularly the need to prevent duplication of prior training competencies while demonstrating the potential for unique milestones.